2017
DOI: 10.4269/ajtmh.17-0019
|View full text |Cite
|
Sign up to set email alerts
|

Importance and Contribution of Community, Social, and Healthcare Risk Factors for Hepatitis C Infection in Pakistan

Abstract: Pakistan has a high prevalence of hepatitis C virus (HCV) infection, estimated at 4.9% (2,290/46,843) in the 2007 national HCV seroprevalence survey. We used data from this survey to assess the importance of risk factor associations with HCV prevalence in Pakistan. Exposures were grouped as community (going to the barbers, sharing smoking equipment, having an ear/nose piercing, tattoo, or acupuncture), healthcare (ever having hemodialysis, blood transfusion, or ≥ 5 injections in the last year), demographic (ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 57 publications
1
30
0
Order By: Relevance
“…Indeed, unsafe therapeutic injections and nosocomial transmission are bigger risk factors for hepatitis C transmission than intravenous drug use. 7,8 An example of this trend was the 2019 outbreak of HIV amongst children in Larkana, Pakistan that was traced back to negligent practices at the health-care centres. 9 This example also challenges the underlying assumption that the largest at-risk group consists of adults older than 30 years.…”
Section: The Cost Of Eliminating Hepatitis C In Pakistanmentioning
confidence: 99%
“…Indeed, unsafe therapeutic injections and nosocomial transmission are bigger risk factors for hepatitis C transmission than intravenous drug use. 7,8 An example of this trend was the 2019 outbreak of HIV amongst children in Larkana, Pakistan that was traced back to negligent practices at the health-care centres. 9 This example also challenges the underlying assumption that the largest at-risk group consists of adults older than 30 years.…”
Section: The Cost Of Eliminating Hepatitis C In Pakistanmentioning
confidence: 99%
“…injections and blood transfusion in health care professionals (27-42.3%) and in the general population (7.8-68%), community-based activities i.e. ear and nose piercing, barbering, and injecting drug use (4,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…One study found intraspousal HCV transmission more common than other intrafamilial transmission [29]. The association found between low S-ES and anti-HCV positivity has been demonstrated previously, including in Thailand [30], the Netherlands [31] and Pakistan [32, 33]. Utilizing advanced molecular diagnostics, such as deep-gene sequencing, could better define transmission patterns within households, elucidating risks and guiding prevention efforts.…”
Section: Discussionmentioning
confidence: 76%